(untitled) (Web of Teachers: Inderscience Research, 2026)
In the current context of medical development, the issues of early diagnosis and prognosis of inflammatory heart diseases in children are becoming increasingly important. A particularly significant role in this process belongs to autoimmune markers, which make it possible to identify not only the presence of immunological damage to heart tissue but also to assess the risk of complications, predict the course of the disease at early stages, and personalize treatment approaches. Cardiovascular diseases in children, especially conditions such as carditis, involve a variety of pathogenetic mechanisms, among which autoimmune processes play a leading role. Their significance is due to the fact that a child’s immune system, due to physiological immaturity, often gives excessive or atypical responses to external and internal stimuli, thereby stimulating the production of autoantibodies.